Вы находитесь на странице: 1из 16

10

.
3 5 .
4 8
6 1 .
5 9 .

I
1.

A2

(sin + cos ) 2 1


1) 0

3) sin2

2) 1

4) cos2


sin

1)

x
3
=
5
2

5
+ 10n ,
3

3)

nZ

n 5
+ 2n , n Z
2) ( 1)

5
+ 2n ,
3

nZ

n 5
+ 2n , n Z
4) ( 1)

A3
x +2
0
7x

1) (-; - 6)

3) (- 1; 8)

2) [-3; 7]

4) [0; +)

4
, [5 ;6 ) .

.
1) [ 5;6 )
2) [ 2;4]
3) ( 3;4]
4) ( 3;2]
5.
1) [0; 4]

3) [3; )

2) [3; 4]

4) (3; 4)

6.

= cos 2 x + 3

= sin x + 2 x 6

1)

' = cos x + 2 x 5

3)

' = cos x +12 x 5

2)

' = cos x +12 x 5

4)

' = cos x + x 5

A7. ,

= 7 x 3 21x 2 +18

1) - 18

3) 21

2) 22

4) 17

x0 = 1

B1. 1,5 3,4cosx, sinx=

15
, < x <
17 2

2. =f(-x)g(x)-g(-x) x0, ,
y=f(x) , y=g(x)-, y=f(x0)=-3, y=g(x0)=-2
C1.

x4
x4 + 1

( ;+)

II
1.

A2

(cos 2 +1)tg 2 1

1) cos 2 ;

3) ctg ;

2) tg ;

4) cos 2 .

A3

4

.
.

5.
1) [-2; 2]

3) [-5; 5]

2) [3; 7 ]

4) [-1; 1]

6.
1)

y = sin x + 4 x 3 ;

3)

y = sin x + x 3 ;

2)
4)

y = 2 sin x + 5

y = cos x + x 4 .

y = sin x + 4 x 3 ;

y = sin x + x3 .

A7. . ,

y = 5 x 2 3x + 2

1) 16;

2) 17;

3) 0,3;

x0 = 2 .

4) 0.

B1. 11 cos x , sinx=

2
, < x <
11 2

2. y=f(x)
5. (-1;4]
f(x)=2-2-1. 3f(7)-4f(-3).
C1.
f(x)=3(2x-4)4-(2x-4)5

x 2 1

III

1.

cos 2 x sin 2 x
2 cos 2 x 1

1) 1;

3) ctg ;

2) tg ;

4) sin .

2. sinx=1
1)

+ 2n, n Z
2

2)

+ n, n Z
2

3)

n, n Z ;

4) 2n , n Z .
5 x 15

3. ( x + 6)( x 8) > 0.
1) ( ;6) ( 3 ;8 ) ;

3) ( 6 ;3 ) ( 8 ;+) ;

2) ( ;6 ) ( 6 ;3) ;

4) ( 3 ;8) ( 8 ;+) .

4.
,

[ 5 ;4 ) .
.
1) [ 5;4 )
2) [ 3;2]
3) [ 3;3]
4) ( 3 ;2] ( 2 ;3]
5.
1) [2; 4]

3) [-2; 6]

2) [3; 5]

4) [-1; 1]

6.

y = 4 cos x

y = sin x + x 3 .

1)

y ' = cos x + 3 x 2 ;

3)

y ' = cos x + x 2 ;

2)

y ' = cos x + x 2 ;

4)

y ' = cos x + 3 x 2 .

7. ,

y = 3 x 2 2 x +1

1) 4

3) 2

2) 1

4) 5

x0 = 1 .

2
5 2

1. 21 sin x , cosx= , < x <

2.

=f(x)

. 6.
f ( 17 ) f ( 11)
,
f ( 29 )

f(5)=3.

1.
f(x)=50(0.5x-1)2-(0.5x-1)

x 3 3

IV
1.

7 sin 2 x 5 + 7 cos 2 + 2

1)

tg 2 ;

3)

2)

1
;
cos 2

4) 4.

2.

sin 2 x =

ctg 2 ;

3
2

n
1) ( 1) + n , n Z ;

n
n
+
,n Z ;
3) ( 1)

n
n+1
+
,n Z ;
2) ( 1)

n
n
4) ( 1) + , n Z .

12
6

3
3
0
2 ( + 6)

4.

1) ( ;6 ) [ 3 ;+) ;

3) ( 6 ;0) ( 3 ;+) ;

2) ( ;6) ( 0 ;3] ;

4) ( 6 ;0 ) [ 3 ;+) .

[ 1;2]

5.
1) [-4; 6]

3) [0; 2]

2) [-2; 2]

4) [4; 6]

6.

y = 1 + 5 cos x

y = 2 x 5 3 cos x .

1)

y ' = 5 x 4 3 sin x ;

3)

y ' = 2 x 4 + 3 sin x ;

2)

y ' = 10 x 4 3 sin x ;

4)

y ' = 10 x 4 + 3 sin x .

7. ,

y = 3 x 2 5 x +1

1) 3

3) 1

2) 8

4) 7

x0 = 2 .

4
5 2

1. sin x , cosx= , < x <


2. y=f(x)
5. ( 1;4]
f(x)=1+2x-x2. 2f(-15)+3f(18).
1. .
f(x)=32(0.5x-3)2-(0.5x-3)

x 7 3

V
1.
1) cos ;

5 sin 2 x 3 + 5 cos 2

3)

1
;
cos

4) tg .

2) 2;

2. cos 2 x sin 2 x =

1) + n , n Z ;

3)

1
2

2
+ 2n , n Z
3

n
n+1
+
,n Z .
4) ( 1)

n
2) ( 1) + n , n Z ;

3.

( 1)( 4 + 2)
+3

1) ( ;3) 2 ;1 ;

3) 3; 2 [1 + ) ;

2) ( 3 ;+) ;

4) [1;+) .

4.

5.
1) [-1; 3]

3) [-4; 4]

2) [-1; 7]

4) (-; 3]

6.

y = 3 4 cos x

y = 2 sin x x 5 .

1)

y ' = 2 cos x 5 x 4 ;

3)

y ' = 2 cos x x 4 ;

2)

y ' = 2 cos x 5 x 4 ;

4)

y ' = 2 cos x x 4 .

7. ,

y = 3 x 2 7 x +12

x0 = 3 .

1) 18

3) 11

2) 23

4) 8
2 3
< x < 2
3 2

1. sin x , cosx= ,
2.

=f(x)

. 6.
f ( 17 ) f ( 11)
,
f ( 29)

f(5)=3.

1.
f(x) =

8
x + 5 ,5 2 ,5
+ 16
2

VI
1.

1-sinx ctgx cosx

1)0

3) 1-sin2x;

2) cos 2 ;

4)sin2x.

2. sin2x=-1
1)

+ n, n Z
4

3) n, n Z

2)

n
+
,n Z ;
4
2

3.

4) + 4n , n Z .

( + 3)( 11)
5

1) ( ;3 ) ( 0 ;11) ;

3) ( ;3) ( 11;+) ;

2) ( 3 ;0 ) ( 11;+)

4) ( 3 ;0) ( 0 ;11) .

4. ,
[3;7]?

5.
1) [-4; 2]

3) [2; 6]

2) [-1; 1]

4) [-2; 6]

6.
1)

y ' = 3 cos x x 5 ;

2)

y ' = 3 cos x 6 x 5 ;

3)
4)

y = 2 4 cos x

y = 3 sin x x 6 .
y ' = 3 cos x 4 x 5 ;

y ' = 3 cos x x 5 .

7. ,

y = 2 x 2 + 3 x + 5

1) 7

3) 0

2) 1

4) 5
4
5 2

1. . sin x , cosx= , < x <

x 0 = 1 .

2. y=f(x)
5. ( 1;4]
f(x)=1+2x-x2. 2f(-15)+3f(18).
1.
f(x) =

5
2 + 4

x + 3 ,5 2 ,5 .

VII

1.

sin 3 sin cos 2


sin 4 cos 4

1) sin

3) cos

2) tg

4) 1.

2. tg 2 x sin x =
1) n, n Z

2) 2 + n, n Z

3)

+ 2n, n Z
4

4)

+ 2n, n Z
2

1
2
sin 2 x

3.
1) 1;

3) 3;

2) 2;

4) 4.

4 2x
0
x 4

4. . .
1) [-1; 2]

Y
2,5

2) [0; 1]

3) [-3; 1]

1,5
1

4) [-3; 0]

0,5
0
-4

-3

-2

-1

-0,5 0

-1
-1,5
-2

5.
1) [-2; 2]

3) [-5; 5]

2) [3; 7 ]

4) [-1; 1]

6.

y = 2 sin x + 5

y = 2 cos x + x 3 .

1)

y ' = 2 sin x + 3 x ;

3)

y ' = 2 sin x + 3 x 2 ;

2)

y ' = 2 sin x + 3 x 2 ;

4)

y ' = 2 sin x + 3 x .

7. ,

y = x 2 + 6 x 4

1) 6

3) 0

2) 5

4) -4

x0 = 3 .

1.

cos 4 2 x sin 4 2 x cos 4 x = tg 3 x

[- ; ].
y=

2.

13
40 60 cos x + 25 cos 2 x
3

1. ,

5 cos 8 x + p = 6 sin 3 4 x

II

III

IV

VI

VII

3
1
2
3
2
2
3
3
10
(-;

4
2
2
2
4
3
2
7
12
(-;

2
1
2
4
2
4
1
4
2

2
3
1
1
1
4
4
0
4

3
1
2
4
2
1
3
3
3

(-;

(-;

(-;

4
2
3
4
4
2
1
3
10
(-;

(-;

-5)U(5;

0)U(1;

-3)U(5;

-3)U(4;

-4)U(9;

-3)U(5;

-5)U(11;

.
.
1
2
3
4
5
6
7
1
2
1

1
4
1
3
2
2
3
7
1